Effects of silodosin, darifenacin, and combination therapy for the treatment of ureteral stent related discomforts - Benedict, Aquinas; Rajenthiran, Vinothkumar; Eswaramurthy, Abhinaya (International Surgery Journal, 2021)
Background: To evaluate the effect of silodosin, darifenacin and combination therapy of two agents in improving the lower urinary tract symptoms of patients with indwelling double-J ureteral stents. Methods: A total of 150 patients underwent placement of a double-J ureteral stent after retrograde ureteroscopy for urinary stone disease. All patients received polyurethane double-J ureteral stents (4 Fr and length 26 cm), which were removed at a mean of around 14 days postoperatively. A total of 40 patients were given no medication (group 1), 39 patients were given silodosin 4 mg once daily (group 2), 40 patients were given darifenacin 7.5 mg once daily (group 3), and 31 patients were given a combination of two agents postoperatively (group 4). International prostate symptom score (IPSS) and visual analogue pain scale (VAPS) questionnaires were completed by each patient at 1st day postoperatively and on the day of stent removal. Results: In the total group of patients, the mean age was 50.24±12.90 years. There was a significant difference in the IPSS total score between group 1 and groups 3 and 4. Group 4 also differed significantly from group 1 in the irritative subscore. The obstructive subscore differed between groups 2 and 4 and group 1. There was a statistically significant difference between group 1 and group 4 in the quality of life (QoL) score. Conclusions: Combination therapy with silodosin and darifenacin improved both irritative and obstructive symptoms more than in the other groups. Combination therapy should be strongly considered for patients who complain of stent-related symptoms.